1996
DOI: 10.2307/1495085
|View full text |Cite
|
Sign up to set email alerts
|

Citizenship Education and Current Educational Reform

Abstract: This article examines the character of citizenship education in Canada as it is represented in the official policy documents of the provinces and territories, as opposed to the actual classroom practice of the curriculum-in-use. We consider policies in light of a typology of citizenship ranging from elitist to activist, and identify common as well as particular features of citizenship education. We find that the official curriculum of educational policy inclines towards an activist conception of citizenship. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 21 publications
0
32
0
1
Order By: Relevance
“…Do you think the reason Iranians, especially youth, came together so quickly during the aftermath of the presidential elections was solely because they wanted an opportunity to see their home country change to their ideal state -an imagined Iran of their past? Or do you think it was driven by a desire to feel a sense of belonging as active citizens (Sears & Hughes, 1996) in Canada, by using a situation with which they felt an affinity as a launching pad?…”
Section: Rominamentioning
confidence: 99%
“…Do you think the reason Iranians, especially youth, came together so quickly during the aftermath of the presidential elections was solely because they wanted an opportunity to see their home country change to their ideal state -an imagined Iran of their past? Or do you think it was driven by a desire to feel a sense of belonging as active citizens (Sears & Hughes, 1996) in Canada, by using a situation with which they felt an affinity as a launching pad?…”
Section: Rominamentioning
confidence: 99%
“…While citizenship is a governing principle of public education, citizenship as a topic has been given particular and explicit attention in schooling through specific courses in citizenship education which have historically been viewed as a central obligation of public schooling (Sears & Hughes, 1996). Particular understandings of citizenship have influenced the aims and objectives of citizenship education.…”
Section: Citizenship Education On the Theoretical Agendamentioning
confidence: 99%
“…Notable in the study, the Canadian material is relatively more conservative. Sears and Hughes's (1996) study of citizenship education across educational jurisdictions in Canada similarly found support for citizenship education that encourages a notion of activism, but they warn that in practice, this tendency is limited. Significantly, textbooks from all three countries focus entirely on national rather than global issues.…”
Section: K Pashby 14mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies conducted in Canada (see, for example, Qué-bec Ministry of Education, 1996;Sears and Hughes, 1996;and Sears et al, 2000) indicate that history and social studies teachers are often reluctant to deal with controversial issues, particularly contemporary and regional/local ones. Lack of time and the degree of familiarity with the issue/subject, as well as the potential negative community reaction, are frequently cited by teachers.…”
Section: Frequency (N=18) Examplesmentioning
confidence: 99%